2013
DOI: 10.1002/nau.22432
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and ejaculatory dysfunction induced by denervation of specific striated muscles anatomically related to the urethra in male rats

Abstract: Striated muscles anatomically related to the urethra contribute differentially to the control of continence and expulsive urethral functions. Damages to the muscles or to their innervation, as may occur during pelvic surgery, would result in sexual and urinary dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
(35 reference statements)
3
11
0
1
Order By: Relevance
“…The female rats in this study demonstrated stereotyped behavior of micturition, similar to that described previously in male rats (24,25). The design of the top of the cage with the food and water container in the center of the jumbo cage VD (B) animals.…”
Section: 56)supporting
confidence: 77%
See 2 more Smart Citations
“…The female rats in this study demonstrated stereotyped behavior of micturition, similar to that described previously in male rats (24,25). The design of the top of the cage with the food and water container in the center of the jumbo cage VD (B) animals.…”
Section: 56)supporting
confidence: 77%
“…The videos were replayed to characterize the female rat's behavior during urine expulsion. In previous studies, it has been described that male rats void at the edges of the cage, mostly in the corners (24,25). To urinate, the rat moves to the edge of the cage, places the rump toward the wall, raises the tail, and expels the urine (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the transection of the caudal branch of the Smb does not abolish the reflex activity of both the Bsm and the Icm in reponse to the penile stimulation or the UGR. It may be that the inactivity of the Pcm reduces the UP and delays ejaculation, which could be related to the reduced fertility ratio reported by other authors, and even to some sexual dysfunctions like retrograde ejaculation . The contraction of the Bsm and Icm could be thus helpful for maintaining ejaculation after the denervation of the Pcm.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, hypothetically, the AUS placement preserving this muscle may decrease the risk of urethral injury during the sharp dissection of its dorsal wall and may also better preserve the flow of blood to the urethra, thus preventing both long‐ and short‐term complications. Moreover, in previous studies assessing the impact of AUS placement for the treatment of SUI, few authors specify having carried out an intervention to preserve the abovementioned muscle and therefore, the possible efficacy and impact of this technique on continence rates has not yet established.…”
Section: Introductionmentioning
confidence: 99%